Evaluating the reduction of stress intensity factor in cracked plates with piezoelectric actuators under mixed mode loading - Awang Hadi Ifwat Awang Bujang (2020)
The characteristics of piezoelectric materials that can be used for actuation and sensing make it an adequate choice for active repair. However, the study on the implementation of active repair using piezoelectric materials is not fully explored, and it lacks practical examples and demonstrations. Hence, the motivations of this thesis are to conduct experiments on active repair using piezoelectric materials on a mixed mode (1 and 2) fracture structure and to observe its effects on the stress intensity factor (SIF). At the same time, to analyse how the active repair is influenced by a certain combination of fracture modes 1 and 2. For the experiments, the normal crack was used. By changing the loading angle on the normal crack specimen, the mixed mode loading (1 and 2) was applied. The approaches that are used for this thesis are mainly experimental approach with a minor finite element analysis (FEA) approach to determine the optimal strain gage locations. The results showed the reductions of SIFs in both modes 1 and 2, and the reductions were varied at certain angles. This study would benefit the repairing structure, especially on aircraft maintenance, where the fracture would occur in several combinations of fracture modes. On the other hand, active repair using piezoelectric materials would reduce the cost of maintenance in the long run.